Life-cycle patterns in male/female differences in job search - Astrid Kunze; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2009)
We investigate whether women search longer for a job than men and whether these differences change over the life cycle. Our empirical analysis exploits German register data on highly attached displaced workers. We apply duration models to analyze gender differences in job search taking into account observed and unobserved worker heterogeneity and censoring. Simple survival functions show that displaced women take longer to find a new job than comparable men. Disaggregation by age groups reveals that these differences are driven by differential behavior of prime age women. There is no significant difference in job search duration among the very young and older workers. These differential outcomes remain even after we control for differences in human capital, and when time dependence and unobserved heterogeneity are incorporated into the model.
Keywords: J31; J63; J64; J71; 330; Gender differences; job search; displaced workers; wage differences; discrimination; Arbeitsuche; Geschlecht; Lebensverlauf; Geschlechterdiskriminierung; Lohndifferenzierung; Statistische Bestandsanalyse; Deutschland